Pursuing Opportunities Through Partnerships: Higher Education and Communities - April Heiselt (The University of Alabama, 2022)
Review of the book: Behringer, B., Bach, B., Daudistel, H., Fraser, J., Kriesky, J., & Lang, G. (2004). Pursuing opportunities through partnerships: Higher education and communities. Morgantown, WV: West Virginia University Press. 277 pages. ISBN 0-937058-93-9 ($45.00)